COMPARATIVE ANALYSIS FOR REACTIVE ENERGY MEASUREMENT METHODOLOGIES, UNDER NON-SINUSOIDAL CONDITIONS IN THREE-PHASE FOUR-WIRE CIRCUITS - Fazio, Alirio [UNESP]; Sampaio, Leonardo P. [UNESP]; Brito, Moacyr A. G. de [UNESP]; A e Melo, Guilherme [UNESP]; Canesin, Carlos A. [UNESP]; IEEE (Ieee, 2011)
This paper presents some methodologies for reactive energy measurement, considering three modern power theories that are suitable for three-phase four-wire non-sinusoidal and unbalanced circuits. The theories were applied in some profiles collected in electrical distribution systems which have real characteristics for voltages and currents measured by commercial reactive energy meters. The experimental results are presented in order to analyze the accuracy of the methodologies, considering the standard IEEE 1459-2010 as a reference. Finally, for additional comparisons, the theories will be confronted with the modern Yokogawa WT3000 energy meter and three samples of a commercial energy meter through an experimental setup.
Keywords: Modern Power Theories; Reactive Power; Non-linear Loads; Unbalanced Circuits; Three-phase Four-wire Circuits; Measurement Errors for Reactive Energy